2000
DOI: 10.1007/bf02322257
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed sympathetic skin response in Parkinson disease

Abstract: The sympathetic skin response (SSR) was used to evaluate sympathetic sudomotor activity in Parkinson disease (PD) and the effects of antiparkinsonian medication on the disease. We recorded SSRs to electric and auditory stimulation in 58 untreated patients with PD and in 20 healthy controls. In addition to amplitude and latency measurements, we examined the number of SSRs evoked by a single stimulus and the response adaptation after repetitive stimuli. The patients with PD subsequently were randomized for admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…A commonly used form of stimulation is to apply a snapping sound of 65 to 105 dB through a pair of headphones [32,33], or a snapping sound along with an electrical stimulation [34].…”
Section: Stimulation Methodsmentioning
confidence: 99%
“…A commonly used form of stimulation is to apply a snapping sound of 65 to 105 dB through a pair of headphones [32,33], or a snapping sound along with an electrical stimulation [34].…”
Section: Stimulation Methodsmentioning
confidence: 99%
“…If the contraction period lengthens, the SSR abnormality becomes more pronounced [16,26,29,31]. SSR abnormalities develop readily in the affected motor side [13,24,25]. In those studies that examined SSR abnormalities in the upper and lower limbs, pathological abnormalities have been reported in only the upper limb [10,14] or both the upper and lower limbs [15,24,26], but there have been no reports of only a lower limb abnormality.…”
Section: Frequency Of Dyshidrosis (Table 2)mentioning
confidence: 97%
“…SSR abnormalities develop readily in the affected motor side [13,24,25]. In those studies that examined SSR abnormalities in the upper and lower limbs, pathological abnormalities have been reported in only the upper limb [10,14] or both the upper and lower limbs [15,24,26], but there have been no reports of only a lower limb abnormality. It has been reported that a disorder progresses upward from a lower limb in the multiple system atrophy (MSA), but a mental sweating disturbance may not necessarily begin from a lower limb in Parkinson's disease.…”
Section: Frequency Of Dyshidrosis (Table 2)mentioning
confidence: 98%
See 2 more Smart Citations